2021
DOI: 10.3390/met11060857
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Physical-Chemical Behaviour Assessment of 3D-Printed CoCrMo Alloy for Orthopaedic Implants

Abstract: In this study, a CoCrMo-based metallic alloy was manufactured using a 3D-printing method with metallic powder and a laser-based 3D printer. The obtained material was immersed in a simulated body fluid (SBF) similar to blood plasma and kept 2 months at 37 °C and in relative motion against the SBF in order to mimic the real motion of body fluids against an implant. At determined time intervals (24, 72, 168, 336, and 1344 h), both the metallic sample and SBF were characterized from a physical-chemical point of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Many researchers [2,3] have studied the effects of large-sized inclusions on the performance of thin-walled tubes, but the effects of small-sized inclusions were rarely discussed. Yang [37] reported that inclusions smaller than 1 μm have no obvious effects on the mechanical properties of alloy.…”
Section: Small-sized Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers [2,3] have studied the effects of large-sized inclusions on the performance of thin-walled tubes, but the effects of small-sized inclusions were rarely discussed. Yang [37] reported that inclusions smaller than 1 μm have no obvious effects on the mechanical properties of alloy.…”
Section: Small-sized Inclusionsmentioning
confidence: 99%
“…As an inevitable metallurgical defect in the alloy, inclusions will significantly reduce the strength, fatigue property, processability, and surface quality of seamless tubes. [1][2][3][4][5][6] For medical alloys, the requirements for purity are becoming increasingly stringent. Especially for medical thin-walled tubes with small diameters, inclusions have become the main factor affecting the properties of tubes, and large-sized inclusions may even cause penetrating defects.…”
mentioning
confidence: 99%
“…This statement is supported by the calculated values of the efficiency of inhibition presented in Table 4. Another medically important material, CoCrMo [77][78][79][80], was the focus of the study conducted by Romas et al [29]. These authors studied caffeine (1,3,7-trimethyl xanthine) as an inhibitor of corrosion of CoCrMo alloy in artificial saliva using electrochemical methods.…”
Section: Magnesiummentioning
confidence: 99%
“…This Special Issue offers a wide scope in the research field around 3D printing, including the following [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]: the use of 3D printing in system design, AM with binding jetting, powder manufacturing technologies in 3D printing, fatigue performance of additively manufactured metals such as the Ti-6Al-4V alloy, 3D-printing method with metallic powder and a laser-based 3D printer, 3D-printed custom-made implants, laser-directed energy deposition (LDED) process of TiC-TMC coatings, Wire Arc Additive Manufacturing, cranial implant fabrication without supports in electron beam melting (EBM) additive manufacturing, the influence of material properties and characteristics in laser powder bed fusion, Design For Additive Manufacturing (DFAM), porosity evaluation of additively manufactured parts, fabrication of coatings by laser additive manufacturing, laser powder bed fusion additive manufacturing, plasma metal deposition (PMD), as-metal-arc (GMA) additive manufacturing process, and spreading process maps for powder-bed additive manufacturing derived from physics model-based machine learning.…”
Section: Contributionsmentioning
confidence: 99%